1998
DOI: 10.1111/j.1600-065x.1998.tb01214.x
|View full text |Cite
|
Sign up to set email alerts
|

Infectious Th1 and Th2 autoimmunity in diabetes‐prone mice

Abstract: In the non-obese diabetic (NOD) mouse, a Th1-biased autoimmune response arises spontaneously against glutamic acid decarboxylase, concurrent with the onset of insulitis. Subsequently, Th1-type autoreactivity spreads intra- and intermolecularly to other beta-cell autoantigens (beta CAAs), suggesting that a spontaneous Th1 cascade underlies disease progression. Induction of Th2 immunity to a single beta CAA results in the spreading of Th2-type T-cell and humoral responses to other beta CAAs in an infectious mann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
43
0

Year Published

2000
2000
2005
2005

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 51 publications
4
43
0
Order By: Relevance
“…Similar to the observations in NOD mice [56,57], the present study showed that the recognition frequency in patients with Type I diabetes for some GAD epitopes, such as B2, GAD65(252±266) decreased with disease progression, whereas the responding rate to other GAD epitopes, such as B4, GAD67(212±226) seemed to increase. No significant differences were found however, in responses to beta and V peptides between recent onset and late onset patient groups.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Similar to the observations in NOD mice [56,57], the present study showed that the recognition frequency in patients with Type I diabetes for some GAD epitopes, such as B2, GAD65(252±266) decreased with disease progression, whereas the responding rate to other GAD epitopes, such as B4, GAD67(212±226) seemed to increase. No significant differences were found however, in responses to beta and V peptides between recent onset and late onset patient groups.…”
Section: Discussionsupporting
confidence: 75%
“…There appears to be a drive towards relative immunodominance of some peptides but also an apparent diversification and broadening of specificity suggesting epitope spreading with disease progression. Studies in autoimmune mouse mod- A B C els show that either initial determinant or spreading determinants could be critical in the pathogenesis of autoimmune diseases [56,57]. Many instances of organ-specific autoimmunity also show such clusters of target determinants that become involved [58].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…206 IL-12 drives the differentiation of T-lymphocytes into the Th1 subset, characterised by production of cytokines leading to cell-mediated immunity. 207,208 Furthermore, in the NOD mouse, IL-12 has been shown to play a primary role in T1D induction, 206,209,210 and in addition, plays a key role in immune reactivity against infections. However, it has been shown that in the absence of infection, IL-12-induced autoreactive T cell responses might predispose to self-destructive immunity.…”
Section: Iddm2-the Insulin Gene (Ins) Regionmentioning
confidence: 99%
“…The CD4 ϩ T cells involved in the mechanisms underlying type 1 diabetes exhibit predominantly a Th1 phenotype, characterized by the secretion of high amounts of IL-2 and IFN-␥ (3)(4)(5). Conversely, CD4 ϩ T cells of the Th2 subset may exhibit regulatory functions that control the development of type 1 diabetes (5, 6).…”
mentioning
confidence: 99%